2015
DOI: 10.1016/j.meegid.2015.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Time scale evolution of avipoxviruses

Abstract: Avipoxviruses are divided into three clades: canarypox-like viruses, fowlpox-like viruses, and psittacinepox-like viruses. Several molecular clock and demographic models available in the BEAST package were compared on three avipoxvirus genes (P4b, cnpv186 and DNA polymerase genes), which enabled to determine that avipoxviruses evolved at a rate of 2-8×10(-5)substitution/site/year, in the range of poxviruses previously reported evolution rates. In addition, the date of mean time of divergence of avipoxviruses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…Tajima's D test of neutrality resulted in a significant negative value (-0.14928), suggesting that this virus might be undergoing a period of evolutionary expansion. A similar pattern of θ values was obtained using partial gene sequences of recently studied avipoxviruses and ORFV, with values ranging from 0.065 to 0.200 [ 9 , 10 ]. These results were consistent with the observed dN and dS values and suggested that selection pressure had altered the rate of evolution.…”
supporting
confidence: 71%
“…Tajima's D test of neutrality resulted in a significant negative value (-0.14928), suggesting that this virus might be undergoing a period of evolutionary expansion. A similar pattern of θ values was obtained using partial gene sequences of recently studied avipoxviruses and ORFV, with values ranging from 0.065 to 0.200 [ 9 , 10 ]. These results were consistent with the observed dN and dS values and suggested that selection pressure had altered the rate of evolution.…”
supporting
confidence: 71%
“…Selection pressure analysis (θ=dN/dS) obtained the value 0.02911 suggested that ORFV under purifying selection. This result coincides with the recently reported θ value of avipoxvirus and ORFV partial genes, which range between 0.065 and 0.200 (Le Loc'h, Bertagnoli, & Ducatez, 2015;Sahu et al, 2019;Velazquez-Salinas et al, 2018). The synonymous (dN) and non-synonymous mutations (dS) drive the selection pressure to fluctuate the evolution rate.…”
Section: Discussionsupporting
confidence: 91%
“…This is supportive of earlier suggestions that some DNA viruses have a long history of co-divergence with their hosts [ 4 ], which in some cases may be a reflection of relatively long durations of infection. Indeed, long-term virus-host associations have been observed in the Herpesviridae [ 1 ], the Poxviridae [ 17 ] and the Polyomaviridae [ 18 ]. However, it is also important to note that we found these viruses contain more instances of host jumping than previously thought.…”
Section: Discussionmentioning
confidence: 99%